2022
DOI: 10.3389/fendo.2022.972033
|View full text |Cite
|
Sign up to set email alerts
|

Lack of placental neurosteroid alters cortical development and female somatosensory function

Abstract: Placental endocrine function is essential to fetal brain development. Placental hormones include neurosteroids such as allopregnanolone (ALLO), a regulator of neurodevelopmental processes via positive allosteric modulation of the GABAA receptor (GABAA-R). Using a mouse model (plKO) in which the gene encoding the ALLO synthesis enzyme is specifically deleted in trophoblasts, we previously showed that placental ALLO insufficiency alters cerebellar white matter development and leads to male-specific autistic-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…In mice, placental metabolism of serotonin is critical for fetal forebrain development. Others have found that placental allopregnanolone deficiency in mice alters cerebellar white matter development and programmes postnatal autistic-like behaviour in the offspring (24). Therefore, these studies suggest a potential link between placental endocrine function, fetal growth and fetal neurodevelopment, which could have long last effects on neurocognitive health outcomes.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In mice, placental metabolism of serotonin is critical for fetal forebrain development. Others have found that placental allopregnanolone deficiency in mice alters cerebellar white matter development and programmes postnatal autistic-like behaviour in the offspring (24). Therefore, these studies suggest a potential link between placental endocrine function, fetal growth and fetal neurodevelopment, which could have long last effects on neurocognitive health outcomes.…”
Section: Introductionmentioning
confidence: 74%
“…However, the placenta is also a powerful endocrine organ that secretes an abundance of hormones and growth factors into the maternal and fetal circulation that allow for fetal development and pregnancy maintenance (15-20). Indeed, there is now growing evidence suggesting that placental metabolism and function impact on fetal brain development (21)(22)(23)(24)(25)(26)(27). For example, in mice, there is genomic linkage between placental and the fetal hypothalamic development (28).…”
Section: Introductionmentioning
confidence: 99%
“…PACAP is produced in both the maternal and fetal compartments and crosses the blood brain barrier 67,68 . Placental factors are often involved in neurodevelopment 69–72 . Our constitutive PACAPko mice are generally bred homozygously, such that neither the fetal nor maternal placental compartments produce PACAP.…”
Section: Resultsmentioning
confidence: 99%
“…67,68 Placental factors are often involved in neurodevelopment. [69][70][71][72] Our constitutive PACAPko mice are generally bred homozygously, such that neither the fetal nor maternal placental compartments produce PACAP. Here, we used dams heterozygous for PACAP crossed with homozygous PACAPko sires to test the effects of placental PACAP in our animals.…”
Section: Adcyap1 Expression (And Pacap Production) In Maternal Placen...mentioning
confidence: 99%
“…Others have found that gestational MIA alters the switch between excitatory and inhibitory signaling in offspring, potentially driven by IL-1R1 activity [ 16 ]. Altered placental production of allopregnanolone in females, a hormone that regulates gamma-aminobutyric acid receptors and therefore the excitatory/inhibitory balance, also contributes to altered behavior [ 6 ]. Therefore, it is possible that gestational MIA results in a female specific effect on the placental programs involved in the excitatory and inhibitory systems.…”
Section: Discussionmentioning
confidence: 99%